Anatomically Abnormal Placement of Placenta and its Under Lying Factors Maternal Tobacco Exposure, History of Cesarean Section and Hypertension among Gravid Females Detected by Sonographically - Riasat Ali Nahra, Hafsah Ehsan Ullah, Areeba Riasat Nahra, M. Faheem Siddiqi, Arif Gulzar, Noor ul Mobeen, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To ascertain, placenta previa, acreta and per acreta by ultrasonography during antenatal visit of pregnant mother in 3rd trimester with history of risk factors smoking active passive, hypertension previous history of surgery with consents. Design: cross sectional. Duration: December 2020 to May 2022 (one year & Six Months). Site: Radiology, Gynae & Obstetric department of Pak Red Crescent Medical & Dental College and teaching hospital Dina Nath Multan Road Kasur. Method: convenient sampling with written consent for participation in study. Pregnant mother in 3rd trimester were examined with ultrasonography and color Doppler. Keywords: Abnormal placement of placenta, Risk factors, Ultrasonography.